Studi Hukum Islam dalam Perspektif Inter dan Multidisipliner: Relevansinya terhadap Dinamika Sosial Modern - Yulfian Yulfian; Syukri Iska; Muhibuttibri; Yuldelasharmi; Jamaludin Hasan (Mutawasith: Jurnal Hukum Islam, 2026)
The study of Islamic law has undergone significant developments in line with the social, cultural, political, and technological dynamics of the modern era. Islamic law is no longer sufficiently understood normatively and textually, but rather needs to be studied contextually through inter- and multidisciplinary approaches. This article aims to analyze the concept, characteristics, and urgency of interdisciplinary and multidisciplinary approaches in the study of Islamic law, as well as their relevance in addressing modern social challenges. The method used is qualitative research with a library approach, through analysis of classical and contemporary literature relevant to Islamic law and the social sciences-humanities. Data collection techniques are carried out through documentation studies, namely by inventorying, reading, and reviewing written sources directly related to the research object. Data analysis is carried out using qualitative-descriptive analysis techniques through a systematic and gradual content analysis approach. The data analysis process is carried out through several steps: (1) data reduction; (2) categorization; (3) interpretation; and (4) drawing conclusions. The main novelty of this research lies in the reorientation of Islamic legal studies from a normative-textual approach to a contextual and dynamic inter- and multidisciplinary approach.